Calculated in Death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2012)
"On Manhattan's Upper East Side a woman lies dead at the bottom of the stairs, stripped of all her valuables. Most cops might call it a mugging gone wrong, but Lieutenant Eve Dallas knows better. A well-off accountant and a beloved wife and mother, Marta Dickenson doesn't seem the type to be on anyone's hit list. But when Eve and her partner, Peabody, find blood inside the building, the lieutenant knows Marta's murder was the work of a killer who's trained, but not professional or smart enough to remove all the evidence. But when someone steals the files out of Marta's office, Eve must immerse herself in her billionaire husband Roarke's world of big business to figure out who's cruel and callous enough to hire a hit on an innocent woman. And as the killer's violent streak begins to escalate, Eve knows she has to draw him out, even if it means using herself as bait" -- from publisher's web site.